Effects of Incorporation of Roasted Soybeans on the Performance of Laying and the Financial Profitability of Laying Hens - Pitala , Were; Sessi, Koami M.; Kulo, Abalo E.; Gbeassor, Messanvi (International Journal of Poultry Science, 2016)
Objective: The test was conducted to determine the effect of the use of roasted soy in the Isa Brown hens breed feeding on egg laying performance and financial profitability. Methodology: Two hundred and eighty Isa Brown hens were divided into four groups and received during 14 weeks of rations at different rates roasted seed of soy "Soja Nyo": 0, 10, 15 and 20%. Each ration was randomly assigned to a batch of 80 hens of 31 weeks old. Results: The incorporation of roasted soy "Soja Nyo" allows an increase in fat and improving energy level schemes. The averages of different rations on the laying rate, using egg weight and feed consumption were significantly different. Conclusion: The best laying rate was obtained with the ration 20%. But the incorporation of roasted soybeans was more efficient at 15% in diets for laying hens according to differential margin.